The Sociology of Loyalty - James, Connor (Springer, 2017)
Chapter 1. Introduction. Chapter 2. Loyalty and Theories of Emotion. Chapter 3. Elements of Loyalty. Chapter 4. Family Loyalty. Chapter 5. National Loyalty. Chapter 6. Sport and Loyalty. Chapter 7. Cultural Loyalty. Chapter 8. Conclusion.